Scotton, P.D., C.D.G. Vanderpool and C. Roncaglia. The Julian Basilica: Architecture, Sculpture, Epigraphy. (Corinth XXII). - Rogers, Dylan K. (Journal of Greek Archaeology, 2023)
pp. 520, 186 b/w figures, 24 b/w plates, 16 color plates, 17 tables, 2 foldouts. Princeton: American School of Classical Studies at Athens, 2022. ISBN: 978-0-87661-023-7 (hardback) € 115.74